2007
DOI: 10.1103/physrevlett.99.131301
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Decaying Axionlike Dark Matter from Clusters of Galaxies

Abstract: We constrain the lifetime of radiatively decaying dark matter in clusters of galaxies inspired by generic Kaluza-Klein axions, which have been invoked as a possible explanation for the solar coronal x-ray emission. These particles can be produced inside stars and remain confined by the gravitational potential of clusters. By analyzing x-ray observations of merging clusters, where gravitational lensing observations have identified massive, baryon poor structures, we derive the first cosmological lifetime constr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…During the last year a number of works appeared, devoted to search for the decay signal of a DM candidate -sterile neutrino -in the X-ray spectra of astrophysical objects [1,2,3,4,5,6,7,8,9]. Indeed, it was noticed long ago [10] that a right-handed neutrino with its mass in the keV range presents a viable warm dark matter (WDM) candidate.…”
Section: Sterile Neutrino As Wdm Candidatementioning
confidence: 99%
See 2 more Smart Citations
“…During the last year a number of works appeared, devoted to search for the decay signal of a DM candidate -sterile neutrino -in the X-ray spectra of astrophysical objects [1,2,3,4,5,6,7,8,9]. Indeed, it was noticed long ago [10] that a right-handed neutrino with its mass in the keV range presents a viable warm dark matter (WDM) candidate.…”
Section: Sterile Neutrino As Wdm Candidatementioning
confidence: 99%
“…Namely, one simply requires that the DM decay line flux in a given narrow energy band does not exceed the total background flux in the same energy bin (c.f. [3,4,5,6,7]). Although such approach does not allow to detect a line, if it is present in the data, it permits to derive a "background model independent" bounds.…”
Section: Sensitivity Of X-ray Telescopes For Dm Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiative decay of keV neutrinos would contribute to the X-ray background [5,30]. Analysis from the X-ray background in clusters provide constraints on the masses and mixing angles of sterile neutrinos [9,31,32,33], and recently it has been suggested that precision laboratory experiments on β decay in tritium may be sensitive to ∼ keV neutrinos [34]. Being weak interaction singlets, sterile neutrinos can only be produced via their mixing with an active species, hence any assessment of the possibility of sterile neutrinos as dark matter candidates or their role in supernovae must begin with understanding their production mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sterile neutrino has a radiative decay channel N → ν + γ, N → ν +γ, producing a narrow line in X-ray spectrum coming from dark matter halos of different astronomical objects. Recently a number of constraints on the mixing angle θ became available, coming from the analysis of X-ray data of Chandra and XMM-Newton satellites [19,20,21,22,23,24,25,26,27]. It is expected that the best results will come from the analysis of dwarf satellite galaxies in the Milky way halo, as having the largest mass-to-light ratios and weakest X-ray background [21].…”
mentioning
confidence: 99%